2008
DOI: 10.1007/s00134-008-1363-6
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in ICU patients with bacterial community-acquired pneumonia: when antibiotics are not enough

Abstract: Mortality remains unacceptably high in immunocompetent patients admitted to the ICU with bacterial pneumonia, despite adequate initial antibiotics and comorbidities management. Patients with shock, acute renal failure and APACHE II score higher than 24 should be considered for inclusion in trials of adjunctive therapy in order to improve CAP survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 34 publications
2
39
1
10
Order By: Relevance
“…Currently, pneumonia guidelines do not emphasise the importance of achieving time-sensitive resuscitation targets in SCAP, although sepsis studies [21,23,24] have consistently demonstrated this to be effective in reducing mortality. Conflicting evidence also exists regarding the usefulness of early antibiotics for SCAP [1,25]. Logically, to achieve outcome improvements, identifying SCAP patients early would not suffice; thus, the pragmatic incorporation of a resuscitation bundle might have improved the outcomes significantly.…”
Section: Respiratory Infections | Hf Lim Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, pneumonia guidelines do not emphasise the importance of achieving time-sensitive resuscitation targets in SCAP, although sepsis studies [21,23,24] have consistently demonstrated this to be effective in reducing mortality. Conflicting evidence also exists regarding the usefulness of early antibiotics for SCAP [1,25]. Logically, to achieve outcome improvements, identifying SCAP patients early would not suffice; thus, the pragmatic incorporation of a resuscitation bundle might have improved the outcomes significantly.…”
Section: Respiratory Infections | Hf Lim Et Almentioning
confidence: 99%
“…Severe community-acquired pneumonia (SCAP) is associated with a high mortality rate (23-50%) and can result in significant healthcare costs [1][2][3]. It is usually defined as community-acquired pneumonia (CAP) that requires intensive care unit (ICU) admission or mechanical ventilation/vasopressor support.…”
Section: Introductionmentioning
confidence: 99%
“…La morbilidad de la decorticación pleuropulmonar por toracotomía puede alcanzar hasta el 30% y la mortalidad al 10%. Las complicaciones más frecuentemente descritas son fístulas broncopleurales, infección de herida operatoria, hemorragias post operatorias y cavidades residuales 1,3,[7][8][9][10]12,[35][36][37][38] . Otras técnicas como la fenestración o la toracoplastía, se dejan para casos extremos en que las otras alternativas quirúrgicas no logran el objetivo de tratar la infección y lograr expansión pulmonar evitando cavidades residuales, de ser posible, deben evitarse ya que se asocian con un deterioro significativo en la calidad de vida de los pacientes 3,10,[29][30][31] .…”
Section: Discussionunclassified
“…El EP en series quirúrgicas mantiene una morbilidad y mortalidad considerables, la morbilidad puede alcanzar el 30% y la mortalidad el 20% en grupos de riesgo [1][2][3][4][5][6][7][8][9]11,38 . Nuestra serie de pacientes globalmente tiene una morbilidad de 30,3% y una mortalidad de 9,0%.…”
Section: Discussionunclassified
“…In this issue of intensive care medicine, Rodriguez et al [6] are reporting non-immunocompromised patients from the CAPUCCI study suffering from severe bacterial CAP (122 S. pneumoniae, 90 non-S. pneumonia pathogens) and receiving adequate antibiotic therapy. Despite appropriate antibiotic therapy of 184 patients with an etiological diagnosis, 43 (23.4%) patients died; risk factors for a fatal outcome in the multivariate analysis were shock (OR 13.0), acute renal failure (OR 4.8) and APACHE II-Score [24 (OR 2.2).…”
mentioning
confidence: 99%